Development and Validation of the Stability-Indicating RP-HPLC Method to Estimate Olaparib in Graphene Quantum Dot Nanoformulation Using Analytical Quality by Design (AQbD) Principles - Rayanade, Pooja; Patil, Archana; Gaude, Yadishma; Salokhe, Abhijit; Shetti, Priya (Indian Journal of Pharmaceutical Education and Research)
Introduction: This study aimed to develop and validate a reliable Reverse-Phase High-Performance Liquid Chromatography (RP-HPLC) method for the accurate quantification of Olaparib in a Graphene quantum dot nanoformulation. The research employed the principles of Analytical Quality by Design (AQbD) to optimize and validate a stability-indicating RP-HPLC method. The primary objective was to optimize key chromatographic parameters, including retention time, theoretical plate count, and tailing factor, to ensure precise and robust analysis of Olaparib formulations. Materials and Methods: A central composite design was utilized to optimize the chromatographic conditions. The method was then validated rigorously to assess its performance characteristics, including accuracy, Linearity, and Limit of Detection (LOD), Limit of Quantification (LOQ), precision, and % RSD. Results: The optimized RP-HPLC method demonstrated excellent performance with a retention time of 4.6 min. The method exhibited high sensitivity with an LOD of 0.4996 μg/mL and LOQ of 1.5139 μg/mL. Precision was demonstrated by a %RSD of less than 2%. The evaluation of stability parameters confirmed the method's suitability for the accurate and precise quantification of Olaparib. Conclusion: This study successfully developed and validated a robust, cost-effective HPLC method for OLA using QbD principles. The method, optimized via CCD, accurately quantifies OLA in both pure and nanoformulation forms, demonstrating excellent stability-indicating properties and broad applicability in pharmaceutical research and development.
Keywords: Olaparib; Graphene Quantum dots; Central composite design; Quality by design; Force Degradation.